Family plots : the de-Oedipalization of popular culture - Heller, Dana A. (Dana Alice), 1959- (Feminist cultural studies, the media, and political culture., 1995)
Family Plots traces the fault lines of the Freudian family romance and holds that the "family plot" is very much alive in post-World War II American culture. It cuts across all genres, insinuating, criticizing, reinforcing, and reinventing itself in all forms of cultural production and consumption. The family romance is everywhere because the family itself is nowhere